Misleading Focal Clinical, Neurophysiologic, and Imaging Features in 2 Children With Generalized Epilepsy Who Underwent Invasive Electroencephalographic (EEG) Monitoring. (May 2020) - Ba-Armah, Duaa; Jain, Puneet; Whitney, Robyn; Donner, Elizabeth; Drake, James; Go, Cristina; Nair, Rajesh Ramachandran; Snead, O. Carter; Weiss, Shelly; Widjaja, Elysa; Yamamoto, Eriko; Ye, Annette; et al.
Children and adults with genetic generalized epilepsy may have focal clinical seizure symptoms as well as electroencephalographic (EEG) findings. This may pose a diagnostic challenge to clinicians, especially when concomitant focal neuroimaging findings exist and the epilepsy is medically refractory. We sought to highlight the challenges that clinicians may face through the description of 2 children with suspected genetic generalized epilepsy who had both focal seizure symptoms and EEG/neuroimaging findings and underwent invasive EEG monitoring. Ultimately, invasive monitoring failed to demonstrate a focal origin for the seizures in both cases, and instead confirmed the presence of genetic generalized epilepsy. We demonstrate that ≥3-Hz generalized monomorphic spike and waves are less likely to represent secondary bilateral synchrony, that focal neuroimaging findings may not always be causal and that repeated hyperventilation is an essential activation procedure for genetic generalized epilepsy.